2020
DOI: 10.1038/s41598-020-59408-2
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 protects retinal pericytes against high glucose-induced oxidative stress through the Nrf2 signaling pathway

Abstract: Oxidative stress has been associated with the etipathogenesis of Diabetic retinopathy (DR). Studies have shown that DJ-1 plays an important role in regulating the reactive oxygen species (ROS) production and resistance to oxidative stress-induced apoptosis. This study aimed to investigate whether DJ-1 upregulates oxidative stress and prevents damage to retinal capillary pericytes by increasing antioxidant capacity through the Nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway. Nrf2 is a redox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Sulforaphane also exhibited similar antioxidative effects in streptozotocin-induced diabetic rats and high glucose-treated Muller cells through the activation of the Nrf2 pathway [54]. Furthermore, activation of Nrf2, either through DJ-1 overexpression [55] or through Nrf2 activators [56], could provide additional benefits to improve retinal pericyte survival and reduce vascular endothelial growth factor-induced cell migration in human retinal microvascular endothelial cells, both involved in the development of DR. In the current study, we have further demonstrated that the Nrf2-ARE pathway can be activated by AST, thereby increasing the expression of HO-1 and NQO1, which in turn attenuates ROS-mediated and intracellular oxidative damage and further protects photoreceptor cells from high glucose-induced apoptosis.…”
Section: Discussionmentioning
confidence: 90%
“…Sulforaphane also exhibited similar antioxidative effects in streptozotocin-induced diabetic rats and high glucose-treated Muller cells through the activation of the Nrf2 pathway [54]. Furthermore, activation of Nrf2, either through DJ-1 overexpression [55] or through Nrf2 activators [56], could provide additional benefits to improve retinal pericyte survival and reduce vascular endothelial growth factor-induced cell migration in human retinal microvascular endothelial cells, both involved in the development of DR. In the current study, we have further demonstrated that the Nrf2-ARE pathway can be activated by AST, thereby increasing the expression of HO-1 and NQO1, which in turn attenuates ROS-mediated and intracellular oxidative damage and further protects photoreceptor cells from high glucose-induced apoptosis.…”
Section: Discussionmentioning
confidence: 90%
“…DJ-1 overexpression enhanced the expression of Nrf2 and its downstream phase II metabolic enzymes, including HO-1, NQO1, GCLC, and GCLM. In contrast, when Nrf2 was inhibited, even if DJ-1 was overexpressed, the expression of phase II metabolic enzymes was not significantly increased, and rat retinal pericyte apoptosis was not significantly reduced (Wang et al, 2020). Protocatechuic acid protected gastrointestinal mucosa cells against ketoprofeninduced oxidative stress by overexpressing DJ-1/Nrf2, while increased antioxidant enzyme expression could be blocked by si-DJ-1 (Cheng et al, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…Nrf2 is normally sequestered in the cytoplasm, which can be activated by signals, such as ROS, which subsequently translocates into the nucleus to regulate expression of downstream antioxidant and detoxificationgenes that counteract ROS ( 31 ). These target genes include glutathione peroxidase, SOD, HO-1, quinone oxidoreductase (NQO1) and GCLC ( 4 , 32 ). Activation of the Nrf2 signaling pathway is one of the critical defensive mechanisms against oxidative stress in a number of tissues, including heart, retina, liver and kidney ( 23 ).…”
Section: Discussionmentioning
confidence: 99%